Effects of Standardized Ileal Digestible Lysine on 15- to 25-lb Nursery Pigs - G. E. Nichols; C. M. Vier; A. B. Clark; M. B. Menegat; H. S. Cemin; C. K. Jones; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; J. C. Woodworth; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 300 pigs (DNA 241 × 600; initial pen average BW of 15.4 lb) were used in a 22-d growth trial to determine the standardized ileal digestible (SID) lysine (Lys) requirement of nursery pigs from 15- to 25-lb. Pigs were weaned at approximately 21 d of age and allotted to pens based on BW and gender. There were 10 replicate pens per treatment and 6 pigs per pen. Pigs were fed a common pelleted diet for 10 d post-weaning. Subsequently, pens of pigs were randomly assigned to 1 of 6 experimental diets in a randomized complete block design, with BW as a blocking factor. Dietary treatments consisted of 1.10, 1.20, 1.30, 1.40, 1.50, and 1.60% SID Lys and were achieved by the inclusion of crystalline amino acids at the expense of corn. Experimental diets were fed for 11 d followed by a common diet fed for 11 d. Experimental data were analyzed using generalized linear and non-linear mixed models, fitting the data with heterogeneous residual variances as needed. Competing models included linear (LM), quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic (BLQ). For the overall treatment period, increasing SID Lys improved (linear, P<0.001) ADG and F/G, with no differences observed in ADFI. Similarly, as dietary SID Lys increased, BW increased linearly on d 11 and 22. Feed cost per pig, feed cost per pound of gain, and total revenue per pig increased (linear, P<0.001) as SID Lys increased, with no observed differences in income over feed cost (IOFC). For ADG, the best-fitting models were the LM and QP models. The maximum mean ADG was estimated at greater than 1.60%, and at 1.54% (95% CI: [1.34,>1.60]%), with 99% of the maximum ADG achieved at 1.43% SID Lys, in the LM and QP models, respectively. Similarly, the best-fitting models for feed efficiency were LM and QP, both estimating the requirement at greater than 1.60% SID Lys. In conclusion, this experiment determined that the mean SID Lys required for nursery pigs from 15- to 25-lb ranged from 1.54% to at least 1.60%. These data provide evidence that different response variables and statistical models can result in different estimates of the requirements. However, formulating nursery diets for 15- to 25-lb pigs to 1.40% would allow for the highest income and approximately 99% of maximum growth to be captured.
Keywords: swine; lysine; growth; modeling